Prompt gravity signal induced by the 2011 Tohoku-Oki earthquake - Jean-Paul Montagner (Nature Communications, 2016)
Earthquakes have been theorised to produce gravity signals that may arrive before seismic waves, but until now they had not been detected. Montagneret al. have detected prompt gravity signals from the 2011 Tohoku-Oki earthquake thus allowing an early warning of earthquakes before seismic wave arrival.